Analisis Etnosains Dalam Pembelajaran IPA di SekolahDasar (SD) Kota Padang Dan Bukittinggi - Atika Ulya Akmal (Universitas Negeri Padang, 2020)
This article seeks to address ethno science employed in the teaching of elementary school. Ethno science is a strategy which creates learning environment and designs learning experience by integrating culture into the learning process at elementary school. Ethnoscience shows authentic instructional materials, classrooms, learning environment, learning method as well as culture-based approach. Learning process would be effective when ethnoscience is integrated in learning topics. Those are, for instance, concerned with rituals, traditional house, traditional medicines and other cultural knowledge relevant to ethnoscience learning. It can be applied through student-centered learning model by such methods as problem based learning, project based learning, discovery, inquiry and process skill. Ethnoscience learning can explore the students’ declarative and constructivist- procedural based knowledge.